Expenditure Issues and Governance in Central America - Corbacho, Ana (IMF Working Papers; Working Paper, 2002)
This paper analyzes Central America's track record on inequality, poverty, and quality of fiscal adjustment in relation to economic growth; health and education outcomes; adequacy of social safety nets; and governance. It then assesses the degree to which the track record can be traced to reforms in public expenditure and governance. Despite the considerable heterogeneity among the countries in the region, there are some policies that all countries need to pursue. Sustained growth and a better quality of fiscal adjustment are needed, as well as policies aimed at increasing individuals' productivity and improving governance.